2019
DOI: 10.3390/nano9111554
|View full text |Cite
|
Sign up to set email alerts
|

DC Self-Field Critical Current in Superconductor/Dirac-Cone Material/Superconductor Junctions

Abstract: Recently, several research groups have reported on anomalous enhancement of the self-field critical currents, Ic(sf,T), at low temperatures in superconductor/Dirac-cone material/superconductor (S/DCM/S) junctions. Some papers attributed the enhancement to the low-energy Andreev bound states arising from winding of the electronic wave function around DCM. In this paper, Ic(sf,T) in S/DCM/S junctions have been analyzed by two approaches: modified Ambegaokar-Baratoff and ballistic Titov-Beenakker models. It is sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…As Raman spectroscopy experiments have revealed, BLG systems can support two phonon modes [5][6][7][8][9][10][11][12][13][14][15], one corresponding to intralayer vibrations and the other to interlayer vibrations. In this spirit, a two-gap superconductivity has been proposed and studied for displaced and commensurate twisted BLG systems [53,56,57]. It was found that, depending on the original stacking order of BLG (being either AA or AB) and the magnitude of the chemical potential, a small in-plane displacement of the pristine layers with respect to each other can drive s-wave and p-wave pairing symmetries into d-wave and f -wave symmetry classes, respectively, and increase the superconducting critical temperature [53].…”
mentioning
confidence: 99%
“…As Raman spectroscopy experiments have revealed, BLG systems can support two phonon modes [5][6][7][8][9][10][11][12][13][14][15], one corresponding to intralayer vibrations and the other to interlayer vibrations. In this spirit, a two-gap superconductivity has been proposed and studied for displaced and commensurate twisted BLG systems [53,56,57]. It was found that, depending on the original stacking order of BLG (being either AA or AB) and the magnitude of the chemical potential, a small in-plane displacement of the pristine layers with respect to each other can drive s-wave and p-wave pairing symmetries into d-wave and f -wave symmetry classes, respectively, and increase the superconducting critical temperature [53].…”
mentioning
confidence: 99%
“…13,14). It is interesting to note that in our previous papers [17,[32][33][34] we found that many atomically thin superconductors, including SLG and topological insulators (with a proximity induced superconducting state) have a two-superconducting band state.…”
Section: Figurementioning
confidence: 69%
“…Figures 5d-f present the analysis of Talantsev et al concerning the superconduting parameters of tBLG samples. The superconducting parameters were derived from fits to the data of the upper critical field, H c2 (T) and the critical current density, J c (T)(self field), following the models by [91][92][93][94][95][96][97][98][99]. All this gives valuable information on the properties of the superconducting state(s) in tBLG samples.…”
Section: Phase Diagrams Of Moiré Superconductors and Comparison With ...mentioning
confidence: 99%